A PROPOSED FRAMEWORK FOR NATURE-BASED TOURISM DESTINATIONS EVALUATION (Jurnal Teknologi (Sciences & Engineering), 2016)
To date, nature-based scholars have been employing a diverse range of attraction evaluation methods mainly derived from the perspective of public perception, policy instrument and resource inventory. Based on its distinctive quality and specific procedure, the physical resource inventory evaluation method is recognized by this paper as a proper means to evaluate attraction of nature-based tourism destinations (NBTD). With the intention of improving both the objectivity and the applicability of NBTD in order to facilitate the assessment methodâ€™s popularization, this paper proposes a universal evolution attraction framework for NBTD. For the purpose of research, this paper reviews the process of physical resources inventory, constructs general assessment structure and designs a scoring system in light of the attractions of NBTD. This paper also discusses the definition of NBTD, the ranking system of attraction assessment and other aspects recognized as necessary parts in the research.Â